Structural and Morphological Evaluations of Natural Hydroxyapatite from Calcined Animal Bones for Biomedical Applications - Olusola Emmanuel Ojo; Olatunde Israel Sekunowo; Margaret Okonawan Ilomuanya; Oluwashina Philips Gbenebor; Samson Oluropo Adeosun (Journal of Casting & Materials Engineering, 2022)
Several biomedical materials have been employed as drug delivery systems, but natural Hydroxyapatite (HAP) has been proven to be exceptionally better than other materials owing to its excellent bioactivity and biocompatibility properties. In this study, natural HAP was obtained from bovine and caprine bones and comparatively analysed for biomedical applications. The bones were hydrothermally treated, calcined in the temperature range of 700–1100°C, held for 2 hours in an electric furnace to remove the organic contents; milled, sifted with 150 μm mesh sieve and then characterized. It was revealed by Energy Dispersive X-Ray Spectroscopy (EDS) that the bovine and caprine bone samples calcined at 1000°C had calcium/phosphorus ratio (Ca/P) of 1.66 closest to the standard of 1.67. The bovine HAP showed the best crystallinity (86.23%) at 1000°C while caprine HAP had its highest (87.25%) at 1100°C. Fourier Transform Infrared Spectroscopy (FTIR) results revealed that the calcination temperature must be greater than 700°C to isolate high quality HAP. The Scanning Electron Microscopy (SEM) showed that the samples calcined at 800°C had the largest average particle size (85.34 μm) while porosity increases with calcination temperature in both samples. The HAP obtained at a calcination temperature of 1000°C proved to have the best quality for biomedical applications.